Osmolyte enhanced aqueous two‐phase system for virus purification. Issue 8 (15th June 2021) - Joshi, Pratik U.; Turpeinen, Dylan G.; Schroeder, Michael; Jones, Bianca; Lyons, Audrey; Kriz, Seth; Khaksari, Maryam; O'Hagan, David; Nikam, Savita; Heldt, Caryn L.
Abstract: Due to the high variation in viral surface properties, a platform method for virus purification is still lacking. A potential alternative to the high‐cost conventional methods is aqueous two‐phase systems (ATPSs). However, optimizing virus purification in ATPS requires a large experimental design space, and the optimized systems are generally found to operate at high ATPS component concentrations. The high concentrations capitalize on hydrophobic and electrostatic interactions to obtain high viral particle yields. This study investigated using osmolytes as driving force enhancers to reduce the high concentration of ATPS components while maintaining high yields. The partitioning behavior of porcine parvovirus (PPV), a nonenveloped mammalian virus, and human immunodeficiency virus‐like particle (HIV‐VLP), a yeast‐expressed enveloped VLP, were studied in a polyethylene glycol (PEG) 12 kDa‐citrate system. The partitioning of the virus modalities was enhanced by osmoprotectants glycine and betaine, while trimethylamine N ‐oxide was ineffective for PPV. The increased partitioning to the PEG‐rich phase pertained only to viruses, resulting in high virus purification. Recoveries were 100% for infectious PPV and 92% for the HIV‐VLP, with high removal of the contaminant proteins and more than 60% DNA removal when glycine was added. The osmolyte‐induced ATPS demonstrated a versatile method for virus purification, irrespective of the expression system. Abstract : Osmolytes were used to preferentially enhance virus recovery in PEG‐citrate aqueous two‐phase system (ATPS). Glycine and betaine preferentially recovered most of non‐enveloped porcine parvovirus and enveloped HIV‐virus like particle in the PEG‐rich phase and left the remaining contaminants from the cell lysates in the citrate‐rich phase. This demonstrated a high recovery and purity of viruses from mammalian and yeast cell expression systems.